2008
DOI: 10.1523/jneurosci.1092-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for Vascular Endothelial Growth Factor (VEGF) Receptor-1 and Its Ligand VEGF-B in Motor Neuron Degeneration

Abstract: Although vascular endothelial growth factor-B (VEGF-B) is a homolog of the angiogenic factor VEGF, it has only minimal angiogenic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 36 publications
3
130
0
2
Order By: Relevance
“…Этот эффект используется для выявле-ния новых возможностей лечения таких заболеваний, как болезнь Альцгеймера и острое нарушение мозгового кро-вообращения [51][52][53][54][55][56].…”
Section: Vegf Bunclassified
“…Этот эффект используется для выявле-ния новых возможностей лечения таких заболеваний, как болезнь Альцгеймера и острое нарушение мозгового кро-вообращения [51][52][53][54][55][56].…”
Section: Vegf Bunclassified
“…It showed both survival effect in laser injury-induced choroidal neovascularization or ischemia-originated retinal neovascularization models, 19 cardiac ischemia mouse, 20 and neuron-protective effect for the brain cortical neurons and retinal neurons 21 and motor neurons in the spinal cord. 22 The two effects may be relatively complemented, since the neural and vascular systems are inseparable and share the common molecular mechanisms for migration. 23 To underlie the survival effects, besides the anti-apoptotic effect via repressing the expression of pro-apoptotic BH3-only proteins and other apoptosis- and cell death-related proteins, including p53 and caspase family members, 21 VEGF-B might potentially enhance energy metabolism by regulating fatty acid (FAs) transport.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the up-regulated transcriptional activation of VEGF-B in response to midbrain neurodegenerative challenges was observed in Parkinson's Disease (PD), and VEGF-B produced by astrocytes and motor neurons exerted a neuroprotective affect. 22 , 100 Preclinical studies in PD 101 and amyotrophic lateral sclerosis model 22 had shown promising results, despite the lack of clinical studies. VEGF-B treatment rescued brain neurons from apoptosis in stroke mouse 21 and protected cultured primary motor neurons against degeneration, 22 with little retinal neovascularization effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations